2013 Sweet Corn Variety Performance Trial, Jay, Florida - Darcy E. P. Telenko; Libbie Johnson; William Wendt (EDIS, 2014)
This 5-page fact sheet summarizes the 2013 sweet corn variety trial at the UF West Florida Research and Education Center Jay Research farm in Jay, Florida. It shows the performance of fifteen commercial and experimental Sh2 (supersweet) sweet corn varieties. This data only represents one year and one location; test results should be considered over several years and locations before final conclusions are valid. Written by Darcy Telenko, Libby Johnson, and William Wendt, and published by the UF Department of Horticultural Sciences, November 2013.